Development of simulation model of the taxi and analysis of the modeling results - Rudi, S. I.; Rudi, A. I. (CriMiCo 2014 : 2014 24th International Crimean Conference Microwave & Telecommunication : conference proceedings : September 7-13, 2014, Sevastopol, Crimea, Russia, 2014)
The results of modeling which were obtained by means of the simulation model of the taxi configured for an average local carrier. There is a description of the executed experiment and explanation of the obtained data results.